(untitled) (Comprehensive Journal of Science, 2026)
This study investigates the phenomenon of estrangement (al-ighrāb) in the poetry of Abu al-Ala al-Maarri, with the objective of identifying its manifestations and assessing its influence on the reading and interpretation of his poetic corpus. Abu al-Ala’s poetry frequently exhibits a distinctive literary strangeness and a complex poetic-philosophical problematic that challenges the reader and stimulates reflection and hermeneutic inquiry. To examine this phenomenon, the research adopts a critical-analytical methodology supplemented by inductive procedures for tracing instances of estrangement across the poet’s oeuvre and for selecting representative textual evidences. The study is structured into an introduction, three main chapters, a conclusion, and a bibliography. Chapter One theorizes the notion of al-ighrāb) by surveying its semantic and critical articulations in classical and modern linguistic and literary criticism, thereby delineating its conceptual parameters as operative in this research. The chapter further contextualizes al-Maarri’s linguistic and intellectual formation and argues that his encyclopedic culture and exceptional memory significantly contributed to the distinctiveness and opacity of his verse. Chapter Two maps the loci of lexical and syntactic estrangement in his poetry, investigates their motivating causes, and evaluates their role in producing textual ambiguity and formal complexity; this chapter engages critically with prior readings by scholars and debates concerning the nature of Abu al-Ala’s poetic language and his rhetorical artifices. Chapter Three examines manifestations of estrangement within his imagery and explores methods of interpretation, highlighting the hermeneutic difficulties encountered by some commentators. The study concludes that the multiple modalities of estrangement observed in Abu al-Ala al-Maarri’s poetry cannot be reduced to mere obscurantism, linguistic deficiency, or limited poetic talent. Rather, estrangement operates as a structural and performative device a deliberate aesthetic strategy through which the poet transcends contemporaneous poetic conventions, asserts the singularity of his style, and demonstrates a remarkable capacity for lexical deployment, semantic innovation, and striking imagistic invention.